A GENDER-BASED ANALYSIS OF STUDENTS’ METACOGNITIVE READING STRATEGIES IN READING ENGLISH - Dedeh rosidah (Journal of English Education Program (JEEP), 2014)
This study is intended to find out the students’ metacognitive reading strategies that were used by male and female students when they were reading English and to find out whether male and female students have typical differences in using their metacognitive strategies. Metacognitive is the way to monitor or regulate cognitive strategies, which include solve a problem, planning for learning, and evaluation after reading activity. This study was conducted by involving fifty one participants that consist of thirty two females and nineteen males at  the eighth grade of a junior high school in Ciamis who completed the questionnaire (Mokhtari & Reichard, 2002). The results showed that males use five strategies and females use fourteen strategies in high frequency. The male students prefer to use problem-solving reading strategies, followed by global reading strategies and support reading strategies. The female students prefer to use problem-solving reading strategies, followed by support reading strategies and global reading strategies. Accordingly, females show higher users of reading strategies than males in each of three sub-categories with the typical differences in overall sub-caregories. From the analysis of the data, it could be concluded that female students’ metacognitive reading strategies of the junior high school in Ciamis was higher than male students. The result of this research can be used as a reference for the further research about the analysis of gender differences to students’ metacognitive reading strategies in reading English. In addition, the other researchers can conduct the study either to compare or follow up this study.Keywords: gender differences, metacognitive, reading strategies.